A misjudged approach to a high accident rate : exploration of accident causes and instructor decisons relating to inexperienced glider pilots - Jarvis, Stephen (Cranfield University, 2009)
Very little research has focussed on inexperienced pilots and there is a notion in literature and popular texts that such pilots are one of the safest groups. Despite this, ‘early-solo’ UK glider pilots were found to have a higher accident rate than any other group. Research was conducted in order to investigate the issues surrounding this. It was identified that accidents sustained by these pilots tended to be initiated by events in the approach and landing phases of fight, and caused by misjudgement of the approach path and landing flare. Most accidents to more experienced pilots were found to be different in all respects. It was subsequently found that instructors believed the highest accident likelihood to be associated with more experience pilots, in line with literature. It was also found that instructors wrongly believed that the ‘approach’ phase was the least likely in-flight phase to be associated with accident causes for low-hours pilots. Critical Incident Technique was used to investigate instructor decisions with regard to sending pilots solo. An initial model of the decision process was put forward. It was found that, with one critical exception, when events occurred on assessment flights that were similar to causal accident factors (from the accident analysis), instructors disallowed solo flight. An absence of potential accident factors was apparently insufficient to allow solo flight by itself; instructors required further evidence in order to confirm that students were ready to fly alone. Exceptionally, pilot performance in terms of the approach path did not appear to be a critical factor when instructors considered disallowing solo flight, highlighting a possible gap in the instructor decision process. It was recommended that further research be conducted to validate and extend the decision model, and that the approach phase be focussed upon more in both training and assessment.